2022
DOI: 10.3390/mi13101694
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Couple Stress and Mass Transpiration on Ternary Hybrid Nanoliquid over a Stretching/Shrinking Sheet with Heat Transfer

Abstract: The present article describes the unsteady flow of a couple stress via a ternary hybrid nanofluid on a stretching surface with porous media. The nanofluid exhibits important properties for increasing heat transmission, and it is widely used in manufacturing and industrial applications. The basic similarity equations have been discovered to accommodate both stretching/shrinking surfaces. Ternary hybrid nanofluid is a colloidal combination of three types of microspheres: Al2O3, single wall carbon nanotubes, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Here, "subscript h" refers to the derivative with respect to h. The radioactive heat flux q r is simplified by Mahabaleshwar et al (2022b). Then equation ( 4) can be written as:…”
Section: Impact Of Ternary Nanofluidmentioning
confidence: 99%
“…Here, "subscript h" refers to the derivative with respect to h. The radioactive heat flux q r is simplified by Mahabaleshwar et al (2022b). Then equation ( 4) can be written as:…”
Section: Impact Of Ternary Nanofluidmentioning
confidence: 99%
“…Convective energy transport in a ternary nanofluid that is moving over a stretching plate was theoretically explored by Manjunatha et al [ 26 ]. Other related recent works can be found in [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al [ 14 ] looked at a nanofluid made of silver and water and found that the silver nanofluid was a better conductor and moved heat well. Several noteworthy works on nanofluids are provided in the following references [ 15 , 16 , 17 , 18 , 19 ]. Daniel et al [ 20 ] investigated a solution for nanofluid flow stretching when the MHD electrical effect is executed with ohmic heating.…”
Section: Introductionmentioning
confidence: 99%